2018
DOI: 10.1016/j.jaad.2017.09.040
|View full text |Cite
|
Sign up to set email alerts
|

Risk of developing pyoderma gangrenosum after procedures in patients with a known history of pyoderma gangrenosum—A retrospective analysis

Abstract: M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…More invasive procedures and patients with chronic disease have a higher risk of developing this subtype. In one retrospective analysis, about 15% of individuals had post-surgical recurrence or exacerbation of existing lesions 24 . PG was often diagnosed as a wound infection at first, leading to debridement and ultimately worsening the lesion because of pathergy.…”
Section: Clinical Presentation and Comorbiditiesmentioning
confidence: 99%
“…More invasive procedures and patients with chronic disease have a higher risk of developing this subtype. In one retrospective analysis, about 15% of individuals had post-surgical recurrence or exacerbation of existing lesions 24 . PG was often diagnosed as a wound infection at first, leading to debridement and ultimately worsening the lesion because of pathergy.…”
Section: Clinical Presentation and Comorbiditiesmentioning
confidence: 99%
“…Adhering to the current recommendations in the literature regarding surgery for PG lesions and the case report of Long et al [11], we were able to perform disease-unrelated surgery free of complications in our described patient. The retrospective study of Xia et al [18] reported only a 15.1% occurrence of PG lesions after surgical procedures; thus, the PG-free course of our arthroplasty surgery cannot be attributed solely to our treatment regimen.…”
Section: Discussionmentioning
confidence: 74%
“…Pathergy has a pivotal role in inducing new post-surgical skin PG in patients with a preexisting diagnosis of PG. However, while cutaneous PG has been frequently reported after surgical procedures involving the skin, especially breast surgery (16), visceral PG involvement is usually not related to previous surgery. This may be due to the fact that visceral PG is a very rare condition and its diagnosis may be difficult to reach.…”
Section: Discussionmentioning
confidence: 99%